Leg and vertical stiffness of transfemoral amputees using running-specific prostheses - Sano, Y.; Hobara, H.; Kobayashi, Y.; Hashizume, S.; Murai, A.; Makimoto, A.; Takemura, H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Since running-specific prostheses (RSPs) emulate spring-like leg functions, human musculoskeletal system is often modelled as a spring-mass model. In the model, the leg (KM) and vertical stiffness (KM) is known to strongly influence running performance. The purpose of this study was to quantify the asymmetry in stiffness between the intact limbs and prosthetic limbs during sprinting. Eight sprinters with unilateral transfemoral amputation performed overground sprinting at maximum speed. & and Kw,t were calculated from vertical ground reaction force data in both the intact and prosthetic limbs. & was significantly greater in intact limbs than prosthetic limbs. Although there was no significant difference on Kvert, cohen's d of Kvert between legs was 1.28. Therefore KM might have potential significant difference.